α–RgIA, a Novel Conotoxin that Blocks the α9α10 nAChR: Structure and Identification of Key Receptor Binding Residues - Ellison, Michael (2008)
α-Conotoxins are small disulfide-constrained peptides from cone snails which act as antagonists at specific subtypes of nicotinic acetylcholine receptors (nAChRs). The 13-residue peptide α-RgIA is a member of the α-4,3 family of α-conotoxins and selectively blocks the α9α10 nAChR subtype, in contrast to another well characterized member of this family, α-ImI, which is a potent inhibitor of the α7 and α3β2 nAChR subtypes. In this study, we have altered side chains in both the 4-residue and 3-residue loops of α-RgIA, and have modified its C-terminus. The effects of these changes on activity against α9α10 and α7 nAChRs were measured, the solution structures of α-RgIA and its Y10W, D5E and P6V analogues were determined from NMR data, and resonance assignments made for α-RgIA[R9A]. The structures for α-RgIA and its three analogues were well-defined except at the chain termini. Comparison of these structures with reported structures of α-ImI reveals a common two-loop backbone architecture within the α-4,3 family, but with variations in side chain solvent accessibility and orientation. Asp5, Pro6 and Arg7 in loop 1 are critical for blockade of both the α9α10 and α7 subtypes. In loop 2, α-RgIA[Y10W] had activity near that of wild-type α-RgIA, with high potency for α9α10 and low potency for α7, and had a similar structure to wild-type. By contrast, Arg9, in loop 2, is critical for specific binding to the α9α10 subtype, probably because it is larger and more solvent accessible than Ala9 in α-ImI. Our findings contribute to a better understanding of the molecular basis for antagonism of the α9α10 nAChR subtype, which is a target for the development of analgesics for treatment of chronic neuropathic pain.